Contrastive Analysis of Noun-Adjective Word Order in Students' Writing: A Case Study of Common Core Classes in a Moroccan Public High School - Zakaria Farid; Achraf Jamali (Journal of English Language Teaching and Linguistics, 2024)
This study explores word order patterns, specifically focusing on the noun-adjective inversion observed in the written language among EFL learners in a Moroccan public high school class. In a case study design with 102 participants, error analysis of learners’ produced language reveals a consistent and frequent deviating pattern as a result of negative transfer from L1 to L2, aligning with the interlanguage hypothesis. The findings enable Moroccan English teachers to predict and address language errors through tailored teaching strategies. Notably, a cross-sectional approach using controlled words unscrambling activity demonstrates the learners’ consistent deviation from English word order, except for instances of familiar phrases, suggesting exposure plays a key role in language accuracy. English teachers in Morocco can significantly profit from these findings by using them to anticipate, react, and modify their teaching strategies. Crucially, using well-known sentences correctly emphasizes how important repeated exposure is to language acquisition